Output power leveling of on-chip thermoelectric generator using a solid–solid phase change material. (15th December 2022) - Nemoto, Kosei; Takeuchi, Ryosei; Baba, Masaaki; Takeda, Masatoshi; Yamada, Noboru
Abstract: Energy harvesting technology using thermoelectric generators (TEG) is a promising solution to environmental energy problems. Moreover, an on-chip TEG, which can improve the net power consumption of electronic devices, is attracting attention. However, thermal or electrical control is required to stabilize the TEG output for unsteady heat sources, such as electronic chips. In this study, we focused on output power-stabilization technology by thermal control using phase-change materials (PCM). A vanadium dioxide (VO2 ) sintered body, a solid–solid PCM, was used as the PCM and compared to paraffin, a typical solid–liquid PCM. The power generation performance of the TEG with these PCMs mounted on a thin heat-generating chip was evaluated. The TEG with VO2 exhibited higher power generation and output power leveling performance than paraffin, mainly because it has a higher thermal conductivity than paraffin. Furthermore, in the TEG with VO2 case, the maximum temperature of the heat-generating chip was 14.4 °C lower than that without the PCM, indicating that the on-chip TEG with VO2 could level the temperature of the electronic chip while generating electricity. Highlights: Output power of a thermoelectric generator was stabilized by phase change material. Vanadium dioxide sintered body and a thermoelectric module were combined. Vanadium dioxide exhibited higher power leveling performance than paraffin.